Farmers' Adaptation Strategies, Coping Behaviour and Barriers to Effective Adaptation to Current Climatic Risks: A Study on Sundarban Region - Rakshit, Shantanu; Padaria, R. N.; Bandyopadhyay, S. (Indian Journal of Extension Education, 2016)
The Sundarban region is one of the worst climate change hotspots that influences the lives and livelihoods of millions  of people. This study was designed to examine the farmers' coping behaviour, adaptation strategies, and barriers to  effective adaptation to current climatic risks. The study was conducted in the Sundarban Region of West Bengal state. Two  villages from Kultoli block of South 24 Parganas district were selected. With 40 respondents from each village, total 80  respondents were selected randomly. The main reported adaptation strategies were crop diversification, change in  cropping sequence, increase of bund height, diversification of income and livelihood. Farmers have shifted from field  crops and fruit orchards to vegetable cultivation. Income from agriculture, fishing and livestock rearing have decreased  and people forced to rely more on daily labour.Mainly reported coping strategies were migration, reduction of daily meal  in amount and frequency, work as a daily labourand alternate income generating activity. The main barriers for effective  adaptation to current climatic risks were lack of resource, lack of knowledge, lack of institutional support, poor extension  system and lack of infrastructure.
Keywords: Adaptation strategies; coping behaviour; barriers